Characterization and acute oral toxicity of concentrated minerals of Pamekasan Madura seawater - Syafika Alaydrus; Abd Kakhar Umar; Sriwidodo Sriwidodo; Ajeng Diantini; Nasrul Wathoni; Riezki Amalia (Wolters Kluwer Medknow Publications, 2021)
Indonesia is a maritime country with abundant seawater mineral content. One of the regions with the highest salt production is Pamekasan Madura. Minerals are known to have many roles and benefits for our bodies, such as regulating fluid balance and metabolism. Therefore, this study aimed to characterize the physicochemical and microbial properties of concentrated minerals obtained through solvent evaporation and salt deposition for ± 60 days. Acute oral toxicity examination was performed as a first step in determining the safety of concentrated minerals to be used as a raw material for drugs. Based on the test results, the concentrated mineral has a clear yellow color, salty taste, and a bit bitter, odorless, with a pH of 6.6 ± 0.21. Concentrated minerals have high mineral content with levels of potassium, sodium, magnesium, boron, and calcium being 44734.1598 ± 12950.4633, 33192.1198 ± 2699.3419, 8738.1388 ± 100.4894, 2092.5715 ± 60.3224, and 276.9704 ± 13.1133 mg/Kg, respectively. The results of microbiological analysis of untreated concentrated minerals (without antimicrobials or sterilization) showed that the total plate count was within limits, including coliform and Salmonella. However, the total mold and yeast levels exceed the threshold. Based on the results of acute oral toxicity testing, the concentrated mineral is practically nontoxic. With high mineral content and low toxicity, it can be concluded that the concentrated minerals from Pamekasan Madura seawater is potential to be used as a raw medicinal material.